2000
DOI: 10.1093/ajcn/72.5.1088
|View full text |Cite
|
Sign up to set email alerts
|

Do adaptive changes in metabolic rate favor weight regain in weight-reduced individuals? An examination of the set-point theory

Abstract: Background: Obese persons generally regain lost weight, suggesting that adaptive metabolic changes favor return to a preset weight. Objective: Our objective was to determine whether adaptive changes in resting metabolic rate (RMR) and thyroid hormones occur in weight-reduced persons, predisposing them to longterm weight gain. Design: Twenty-four overweight, postmenopausal women were studied at a clinical research center in four 10-d study phases: the overweight state (phase 1, energy balance; phase 2, 3350 kJ/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
144
4
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(163 citation statements)
references
References 38 publications
11
144
4
4
Order By: Relevance
“…Although voluntary dietary restriction is a common intervention for obese patients, it is usually accompanied by a decrease in energy expenditure, at least in the short-term. 13 In evolutionary terms, this can be considered an adaptive trait which occurs in order to conserve energy. However, this contributes to the difficulty experienced by obese individuals who attempt to diet A significant increase in plasma insulin was demonstrated after oxyntomodulin injection (***P ¼ 0.0003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although voluntary dietary restriction is a common intervention for obese patients, it is usually accompanied by a decrease in energy expenditure, at least in the short-term. 13 In evolutionary terms, this can be considered an adaptive trait which occurs in order to conserve energy. However, this contributes to the difficulty experienced by obese individuals who attempt to diet A significant increase in plasma insulin was demonstrated after oxyntomodulin injection (***P ¼ 0.0003).…”
Section: Discussionmentioning
confidence: 99%
“…7 Increased sedentary behaviour is an important factor in the development of human obesity. 10 Whilst low-resting energy expenditure may contribute to obesity, 11,12 recent research has indicated it has minimal impact on weight gain 13,14 and activity-related energy expenditure may be much more important. 15 It has been reported that low physical activity accounted for 77% of weight gain over a year in one prospective study 16 and inactivity is a major determinant of increased adiposity during overfeeding.…”
Section: Introductionmentioning
confidence: 99%
“…This experimental paradigm enables the effects of weight Brought to you by | University of Sydney Library Authenticated Download Date | 1/24/17 4:17 AM loss per se to be examined, independent of any effects of energy restriction. Indeed, certain adaptations to energy deficit, notably reduced metabolic rate and impaired thyroid function, are seen when measured during energy restriction but not after a period of 10 days to 3 months in energy balance in weight-reduced individuals [58,59]. As such, it is reasonable to propose that HPA axis function may be different depending upon whether it is measured during energy restriction or following a period of weight maintenance at the reduced body weight.…”
Section: Effects Of Energy Restriction On Activity Of the Hpa Axis Inmentioning
confidence: 99%
“…Such a calculation fails to account for how an individual's energy expenditure adapts to the energy deficit and decreasing body weight and she will therefore not reach her weight loss goal. The magnitude of the expected energy expenditure adaptation during weight loss is a much debated issue [32][33][34][35][36] and has not been addressed in the present study.…”
mentioning
confidence: 92%